I Vulnera of the punitive system of legal persons for international corruption in the light of european union law principles (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
Starting from a judgement of the court of first instance of Milan about an international corruption case affair, the article highlights a disparity in sanctions for administrative corporate criminal liability, which is analyzed in the light of the adequacy of sanctions in connection with the principles of European Union law.
Keywords: international corruption, corporate criminal liability, E.U. Law, infringement procedure, principle of proportionality